2008
DOI: 10.1021/es801549w
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Iodine and Perchlorate and Excretion in Human Milk

Abstract: Perchlorate, thiocyanate, and iodine excretion in urine and milk of 13 breastfeeding women was investigated and the results were interpreted by a model of parallel/competitive transport of these species by the sodium iodide symporter. For each species i, we assumed physiological homeostasis, where i T,in equals the corresponding total excretion in urine and milk (i e,u + i e,m ). The fraction of the total excretion that appeared in milk f i,m was measured and ranged from 0.394-0.781, 0.018-0.144, and 0.086-0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 44 publications
5
70
1
Order By: Relevance
“…Recent studies, among which 57 women were the largest sample, report a range of median breast milk iodine levels from 35-155 lg/L (8,32,(40)(41)(42). We reported that the median breast milk iodine concentration in 57 Boston-area women was 155 lg/L (8), similar to that of a 1984 study of 37 women (178 lg/L), but higher than those (33.5, 37.9, 43.0, 55.2, and 71.3 lg/L) reported recently in four studies (32,40,41,43) and in the present report. Kirk et al reported that breast milk iodide and perchlorate levels were inversely correlated in six samples with perchlorate concentrations of ‡ 10 lg/L, although there were no correlations between breast milk iodide and perchlorate in the full data set (32).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, among which 57 women were the largest sample, report a range of median breast milk iodine levels from 35-155 lg/L (8,32,(40)(41)(42). We reported that the median breast milk iodine concentration in 57 Boston-area women was 155 lg/L (8), similar to that of a 1984 study of 37 women (178 lg/L), but higher than those (33.5, 37.9, 43.0, 55.2, and 71.3 lg/L) reported recently in four studies (32,40,41,43) and in the present report. Kirk et al reported that breast milk iodide and perchlorate levels were inversely correlated in six samples with perchlorate concentrations of ‡ 10 lg/L, although there were no correlations between breast milk iodide and perchlorate in the full data set (32).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main health hazards is connected with the very fact that perchlorate interferes with iodide uptake in the thyroid gland [35,36]. In large doses, it has been linked to anemia and fetal brain damage [30,35].…”
Section: Clomentioning
confidence: 99%
“…Similarly, the concentrations of perchlorate found in breast milk in Nanchang, China were 3e8 times greater than the values reported from the U.S. (Fig. 1, mean: 5.80e10.6 ng mL À1 , median: 2.50e7.30 ng mL À1 ) (Borjan et al, 2011;Dasgupta et al, 2008;Kirk et al, 2007Kirk et al, , 2012Kirk et al, , 2005Leung et al, 2012;Leung et al, 2009). It is a tradition in China to display fireworks and firecrackers during celebration; in Nanchang city, approximately 376 tons of fireworks trashes were generated in 2012 during the 7-day Chinese New Year celebration.…”
Section: Comparison With Other Studiesmentioning
confidence: 71%
“…1. To our knowledge, nearly all previously studies on perchlorate in the breast milk, infant formula and urine of infants were from the U.S. (Borjan et al, 2011;Dasgupta et al, 2008;Kirk et al, 2007Kirk et al, , 2012Kirk et al, , 2005Leung et al, 2012;Leung et al, 2009;Pearce et al, 2007;Valentin-Blasini et al, 2011), but several studies reported perchlorate concentrations in infant formula from Canada (Wang et al, 2011), Korea (Her et al, 2010;Lee et al, 2012) and Japan (Asami et al, 2013). The urinary concentrations of perchlorate that were detected among all infants from Nanchang, China were up to 20 (range: 2e20) fold higher than those of American infants (Fig.…”
Section: Comparison With Other Studiesmentioning
confidence: 90%
See 1 more Smart Citation